Chemodectoma in a Bitch - Souza, Tayza Jayme; Chimenes, Natielly Dias; Caramalac, Silvana Marques; Guizelini, Carolina de Castro; Babo-Terra, Veronica Jorge; Palumbo, Mariana Isa Poci (Acta Scientiae Veterinariae, 2022)
Background: Chemodectomas, better known as tumors of the base of the heart, arise from aortic bodies, respiratory chemoreceptors located near or inside the aortic arch or originate from receptors located in the carotid arteries. Relatively rare, they affect dogs and, to a lesser extent, felines. They gain great importance when they influence the function of the cardiovascular system, with animals showing clinical signs related to congestive heart failure. Clinical diagnosis is based on symptomatology and complementary tests such as radiography, electrocardiography and echocardiography, while the definitive diagnosis is obtained by cytological and histopathological exams. This study aims to reports a case of malignant chemodectoma in a bitch, whose main symptomatology was neurological and not cardiovascular. Case: A 1-year-old Rottweiler bitch was attended with neurological alterations compatible with vestibular syndrome, hyporexia, dysphagia, apathy, melena, emesis, and purulent nasal discharge on the right nostril. On physical examination, the animal showed depressed level of consciousness, poor body condition, bilateral quemosis, paralysis of the right eye, inspiratory dyspnea and muffling of cardiac auscultation, besides a subcutaneous nodule between the scapulae. On neurological evaluation, horizontal nystagmus, head tilt to the right side, ventromedial strabismus and facial nerve paralysis on the right side were observed so that the localization of the lesion was set in peripheral vestibular system. During anesthesia for esophageal tube placement, a mass from the hard palate to the oropharynx was noted, making endotracheal intubation impossible to perform. Biopsy of this nodule was performed, and tracheostomy was indicated, but the owner opted for euthanasia before the procedure. Necropsy revealed white soft masses in the bilateral retromandibular region, on the subcutaneous tissue near the scapulae, in the right ear and since nasopharynx to the soft palate, in addition to sparse white nodules in the heart, lung, carotid artery, kidneys, right ovary, mesentery near to the spleen, and axillary lymph node. Histologically, the nodules were characterized by neoplastic cells population organized in short bundles or cords, arranged around small blood vessels surrounded by delicate connective tissue. Neoplastic cells infiltrated muscles and blood and lymphatic vessels were filled by multiple neoplastic emboli. The histological pattern of the cells allowed the diagnosis of chemodectoma. Discussion: The bitch from this case had 1-year-old when diagnosed with chemodectoma, differently from most cases from literature, that are between 7 to 15 years old. Furthermore, primarily cardiac tumors are considered rare, being chemodectoma the most common, often reported in Boxer and Boston Terrier dogs, but unusual in Rottweilers. Despites some articles mentioning seizure and Horner Syndrome secondary to a carotid body chemodectoma, neurological signs are not commonly observed in these cases. The presence of the tumor in the middle ear region of the right side supports the occurrence of peripheral vestibular syndrome and facial nerve paralysis on the same side. Because it is a neoplasm that is usually detected late during the course of the disorder, most patients either cannot obtain diagnosis in vivo, as in this reported animal, which was in such a critical condition that underwent euthanasia, or there are no more possible therapeutic choices. In the patient described, there were numerous metastatic masses and nodules spread throughout the body. Although the typical clinical signs in animals with chemodectomas are often related to heart disease, neurological signs may also be present. This report emphasizes the importance of chemodectoma being included as a differential diagnosis in young dogs and even in breeds such as Rottweiler. Keywords: aortic body neoplasia, paraganglioma, vestibular syndrome.